Conservative management of a ruptured mycotic aneurysm. (15th May 2013) - Lodge, Freya; Conway, Nerys; Waterfield, Nick
Abstract : Mycotic aneurysms are a well-recognised complication of infective endocarditis. In contrast to many sequelae of endocarditis, they can present late in the course of the disease, despite adequate treatment. We discuss the case of an 82-year-old patient who was successfully treated for Enterococcus faecalis endocarditis, but presented late with a hypotensive collapse. CT imaging demonstrated a ruptured mycotic aneurysm. He underwent laparotomy, but the decision was made to treat conservatively to protect the vascular supply to the bowel. The patient subsequently made a full recovery.